Macroecological patterns and correlates of ant–tree interaction networks in Neotropical savannas - Dáttilo, Wesley; Vasconcelos, Heraldo L. (Global ecology and biogeography, 2019)
Aim Similar to species richness, ecological interactions can vary across latitudinal and environmental gradients. Knowing the patterns and drivers of such variation could help us to better understand the role of species interactions in maintaining biodiversity. In this study, we analysed the macroecological patterns of the structure and interaction beta diversity of interaction networks involving trees and ants. Location Twenty‐nine sites encompassing 20 degrees of latitude throughout the Neotropical savanna. Time period 2010–2015. Major taxa studied Trees and arboreal nesting ants. Methods For each site, we built an interaction network and calculated network size, interaction diversity (Shannon diversity of interactions), specialization, modularity, nestedness, and interaction dissimilarity (contribution of each network to the regional pool of possible interactions). We also determined how interaction beta diversity varied among all sampling sites. Net primary productivity (NPP), temperature and rainfall were evaluated as potential correlates of the observed changes in network descriptors and interaction beta diversity. Results We found no latitudinal gradient in network specialization, nestedness or modularity. However, sites at higher latitudes had larger networks, higher interaction diversity and higher interaction dissimilarity, and this was correlated mainly with the latitudinal variation in NPP. Interaction rewiring generated by the reassembly of the interactions between the same species in different sites was the main contributor to the total interaction beta diversity. However, the level of interaction rewiring was independent of the geographical and environmental distance between sampling sites. Main conclusions Ant–tree network structure remained relatively invariant across the latitudinal and environmental gradient possibly due to high interaction rewiring among the partners. Moreover, our findings show that more productive sites, located at higher latitudes, have high dissimilarity to the regional pool of possible interactions (i.e., strong interaction filtering), indicating that these sites significantly contribute to the maintenance of interaction biodiversity in Neotropical savannas.